Mekanisme Pembuatan Briket Berbasis Limbah Pertanian yang Ramah Lingkungan - Febi Navila Ella Firdani; Sudarti Sudarti (PROGRAM STUDI MESIN DAN PERALATAN PERTANIAN, 2022)
The problems that are often encountered are the problem of garbage or waste from human activities, these activities include households, agriculture, factories, and others. The purpose of this research is to reduce waste or waste that is really needed at this time whether it is used for other alternative sources that are environmentally friendly, so that waste or waste from agricultural activities does not continue to increase, organic fertilizer and briquettes or charcoal can be used. In this study using the method of literature review from various international journals. The journal used starts from the past 10 years, namely 2012-2022 and searches for it via Google Scolar. Keywords used when searching journals on Google Scolar such as